Implementation of Aquaponic Technology in Fish Cultivation Groups in Ngemplak Hamlet, Kapanewon Turi, Sleman Regency - Rinasa Agistya Anugrah; Ferriawan Yudhanto; Ita Apriani; Desi Susilawati (Peneliti Teknologi Teknik Indonesia, 2022)
Post-pandemic society is required to become a food-independent society, capable of producing raw food sources through agriculture, animal husbandry, and fisheries. Through aquaponics technology, people can apply effective new technology to increase food security and independence. Aquaponic technology is a technology in aquaculture and plant cultivation combined with increasing the effectiveness of cultivation and the quality of crop yields to accelerate the growth of fish and plants. Ngemplak Hamlet, Donokerto Village, Turi Sub-district, Sleman District is a hamlet with potential for fish cultivation. There are a lot of fishery business actors because the water is clean and abundant, so until now, there are 17 business actors in the fishery sector. However, they move independently in developing their business. There is no fish farming community in this village. The district also does not yet know and apply aquaponics technology. The implementation method in this service is FGD with hamlet equipment for forming fish farming groups and increasing knowledge and skills of aquaponics technology; counseling and training are carried out with this theme. As a result, a fish farming group and its organizational structure has been successfully established. All members of Ngemplak hamlet fish farming know Aquaponic Technology, and 90% of them have been able to implement Aquaponic Technology in their respective ponds.